Syndecan-4 promotes vascular beds formation in tissue engineered liver via thrombospondin 1. Issue 1 (1st January 2020) - Hu, Xiaoyi; Chen, Junjie; Huang, Hechen; Yin, Shengyong; Zheng, Shusen; Zhou, Lin
ABSTRACT: Instantaneous blood coagulation after bioengineered liver transplantation is a major issue, and the key process in its prevention is the construction of the endothelial vascular bed on biomimetic scaffolds. However, the specific molecules involved in the regulation of the vascular bed formation remain unclear. Syndecan-4 is a type I transmembrane glycoprotein commonly expressed in the human body; its receptor has been reported as critical for optimal cell adhesion and initiation of intracellular signaling, indicating its promising application in vascular bed formation. In the current study, bioinformatics analysis and in vitro experiments were performed to evaluate whether syndecan-4 promoted endothelial cell migration and functional activation. Exogenous syndecan-4-overexpressing endothelial cells were perfused into the decellularized liver scaffold, which was assessed by Masson's trichrome staining. Western blotting and qRT-PCR were used to evaluate the effects of syndecan-4 on the thrombospondin 1 (THBS1) stability. We found that syndecan-4 promoted the adhesion of vascular endothelial cells and facilitated cell migration and angiogenesis. Furthermore, syndecan-4 overexpression resulted in a well-aligned endothelium on the decellularized liver scaffolds. Mechanistically, syndecan-4 destabilized THBS1 at the protein level. Therefore, our data revealed that syndecan-4 promoted the biological activity of endothelial cells on the bionic liver vascular bed through THBS1. These findings provide scientific evidences for solving transient blood coagulation after bionic liver transplantation. Graphical abstract: